2019
DOI: 10.1029/2019wr024836
|View full text |Cite
|
Sign up to set email alerts
|

Threshold of Motion Conditions Under Stokes Flow Regime and Comparison With Turbulent Flow Data

Abstract: The present study numerically investigates the effects of bed geometrical properties on particle entrainment driven by Stokes flow. We use different substrate arrangements to alter two important factors: The angle of repose, φ, and degree of exposure, e, of the test particle. The effectiveness of shear flow in mobilizing surface particles will change with e and φ, or collectively, η = e/tanφ, yielding a wide range of critical Shields parameter, θ c , values. The use of η is better suited for describing local b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 78 publications
(180 reference statements)
0
7
0
Order By: Relevance
“…For example, the transition point (Θ, Q * ) ≈ (0.05, 0.007) at which the function Q * (Θ) measured in the gravel-bed experiments by Paintal (1971) changed from Q * ∝ Θ 16 to Q * ∝ Θ 2.5 (see section 1) is indistinguishable from the reference threshold for the same conditions within measurement uncertainty. In particular, a close examination of Paintal's and other gravel bed data has revealed that Paintal's power-16 region can actually be subdivided into two regions (Dey & Ali, 2019, Figure 5) (see also Shih and Diplas, 2019, Figure 8b): one region (Θ ≲ 0.04) with a milder power law and one with a stronger power law (0.04 ≲ Θ ≲ 0.05), which includes a jump of Q * by an order of magnitude at Θ ≃ 0.04. Such a jump is consistent with exceeding the rebound threshold Θ Rb t because transported particles suddenly become able to move along the surface for comparably long times before being captured by the bed.…”
Section: Does the Shields Diagram Truly Show Incipient Motion Threshomentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the transition point (Θ, Q * ) ≈ (0.05, 0.007) at which the function Q * (Θ) measured in the gravel-bed experiments by Paintal (1971) changed from Q * ∝ Θ 16 to Q * ∝ Θ 2.5 (see section 1) is indistinguishable from the reference threshold for the same conditions within measurement uncertainty. In particular, a close examination of Paintal's and other gravel bed data has revealed that Paintal's power-16 region can actually be subdivided into two regions (Dey & Ali, 2019, Figure 5) (see also Shih and Diplas, 2019, Figure 8b): one region (Θ ≲ 0.04) with a milder power law and one with a stronger power law (0.04 ≲ Θ ≲ 0.05), which includes a jump of Q * by an order of magnitude at Θ ≃ 0.04. Such a jump is consistent with exceeding the rebound threshold Θ Rb t because transported particles suddenly become able to move along the surface for comparably long times before being captured by the bed.…”
Section: Does the Shields Diagram Truly Show Incipient Motion Threshomentioning
confidence: 98%
“…Thus, the yield stress of the bulk granular material may at least play some role in setting the scatter in normalΘtmax. In this context, it is worth noting that, for the entrainment of particles resting on an idealized substrate by a laminar flow, threshold Shields numbers range from zero to very large values depending on the packing arrangement (Agudo et al, ; Deskos and Diplas, ; Shih and Diplas, ; Topic et al, ).…”
Section: Yield and Flow Of Dense Granular Media In The Context Of Sedmentioning
confidence: 99%
“…The calculation of F D that act on a partly exposed particle without resolving the flow field has been one of the most challenging issues. In this study (Shih & Diplas, 2019), we first define the exposure e as e=Ae/At where A e and A t are the exposed and total particle areas projected on a plane perpendicular to the flow, respectively.…”
Section: Model and Methodsmentioning
confidence: 99%
“…For intermediate states (0 < e < 1), Shih & Diplas (2019) showed that the fluid drag force increases linearly with exposure. Thus, the fluid drag force can be expressed as FD=eboldFfalsêD4.399998em()0e1 …”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation